Reinterpreting Qur'anic Themes: Muṣṭafa Muslim's Approach to Mauḍū'ī Tafsir - Farhan, Rivki Lutfiya; A. Sabiqul Himam; M. Abdul Ghofur (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This article delves into Muṣṭafa Muslim's method of mauḍū'ī tafsir, emphasizing the process of reinterpreting themes found within the Qur'an. The research methodology employed is library-based, utilizing an analytical framework. It commences with identifying primary sources pertinent to the research focus, particularly literature concerning Qur'anic interpretation, with a specific emphasis on the mauḍū'ī approach. The primary focus lies on Muṣṭafa Muslim's work